Disruptive Finance : Using Psychometrics to Overcome Collateral Constraints in Ethiopia - Alibhai, Salman; Buehren, Niklas; Coleman, Rachel; Goldstein, Markus; Strobbe, Francesco (World Bank, Washington, DC, 2018)
This case study tells the story of the evolution of psychometric credit scoring as an innovative solution in a World Bank operation, from its humble beginnings as a small pilot in Ethiopia, to the current movement to replicate its use for similar challenges in countries across the continent in Tanzania, Zimbabwe, Madagascar, and beyond. Fintech is commonly defined as an industry composed of companies that use technology to make financial systems more efficient. The story is one of both achievements and setbacks, just as the future of fintech holds both promise and limitations. It is shared with a view to better understand how psychometrics and fintech more broadly can be utilized to solve critical development challenges, and help get finance to those who need it most around the world.